Pengaruh Kualitas Pelayanan terhadap Volume Penjualan : Studi Kasus pada Usaha Mini Market Madina Sejahtera di Dalan Lidang Kecamatan Panyabungan Kabupaten Mandailing Natal - Siti Aminah Harahap; Muhammad Ardiansyah; Andy Hakim (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The purpose of this study was to determine the effect of service quality on sales volume at the Madina Sejahtera mini market in Dalan Lidang, Panyabungan District, Mandailing Natal Regency. The research ethod used is a quantitative method by describing data using purposive sampling. The sample of this study was 100 people using a quantitative approach with the help of SPSS version 21. Data analysis using the t test obtained the results of t count 14.053 and t table at a significance level of 5% of 1.664, so t count > t table. This shows that there is an effect of service quality on sales volume in Dalan Lidang, Panyabungan District, Mandailing Natal Regency.